The Effect of Using Social Media Towards Students' Motivation and Learning Outcomes During the Covid-19 Pandemic - Ilpi Zukdi; Naila Hayati; Reza Febria Sari; Ciptro Handrianto; Syuraini Syuraini; Zulfahmi HB (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
The Covid-19 pandemic has changed the learning process which was initially carried out face-to-face at school into distance learning at home. This is an effort to prevent the spread of Covid-19. Of course, an effective learning media is needed to support the learning process. This study aims to determine the effect of using social media on students' motivation and learning outcomes during the Covid-19 pandemic. This type of research is ex-post facto quantitative research. The populations in this study were students of class XII IPA and IPS MA Negeri 1 Solok Plus Keterampilan as many as 169 people. By using random sampling technique, a sample of 51 students was obtained. Data was collected by using questionnaires and documentation techniques. To analyze the data, this study used simple linear regression analysis. The results showed that: (1) There was a significant effect between the use of WhatsApp social media on the motivation to learn Al-Qur'an Hadith in class XI at MA Negeri 1 Solok Plus Keterampilan. This is evidenced by the obtained significance value of 0.000. Because the significance value is (p) 0.05, then Ha is accepted and H0 is rejected. (2) There is no significant effect between the use of WhatsApp social media on the learning outcomes of Al-Qur'an Hadith class XI at MA Negeri 1 Solok Plus Keterampilan. This is evidenced by the obtained significance value of 0.560. Because the significance value is (p) 0.05, then Ha is rejected and H0 is accepted. The recommendations of this research are: Principals should be able to give freedom to educators to use media that can support online learning. The school principal must also provide supporting facilities so that online learning can run effectively. Educators can make optimal use of the use of WhatsApp as an online learning medium or as a communication medium to increase students' learning motivation. Educators are expected to find alternatives in order to improve learning outcomes in using WhatsApp as an online learning medium.